Exploring Self-Regulated Learning Strategies and Academic Performance among Orphanage Secondary School Students - Rahmadhani, Devy Yuniastuti; Budiraharjo, Markus (Lectura : Jurnal Pendidikan, 2024)
This study investigated the self-regulated learning strategies employed by secondary school students living in Panti Asuhan Bahagia Sampit. It attempted to reveal some variables influencing their self-regulated learning strategies in relation to their academic achievement. Using a qualitative research methodology and a narrative approach, the study was laid upon a social cognitive theory. Drawing from 45 children as the population of the study, six participants were selected for the study using purposive sampling. Each participant was interviewed twice, with each lasting for about 30 minutes. The findings demonstrated that those exhibiting high levels of self-regulation outperform those exhibiting low levels of self-regulation or lacking self-regulated learning. Personal, behavioral, and environmental factors all had an impact on how students underwent self-regulated learning. The study is set to offer efficient interventions to help secondary school children from orphanages succeed academically by examining those areas.